Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/polym13091380
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic Polyurethane Foam with Keratin and Flame-Retardant Additives

Abstract: Viscoelastic polyurethane (VEPUR) foams with increased thermal resistance are presented in this article. VEPUR foams were manufactured with the use of various types of flame retardant additives and keratin fibers. The structure of the modified foams was determined by spectrophotometric-(FTIR), thermal-(DSC), and thermogravimetric (TGA) analyses as well as by scanning electron microscopy (SEM). We also assessed the fire resistance, hardness, and comfort coefficient (SAG factor). It was found that the use of ker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Around 5.5% (0.112 kg) of a chicken's weight is feathers [25], with annually 6.3 million tonnes being produced as a waste product worldwide. Feathers are currently used in low value uses such as composting, fertilizer or for pet food [26,27] despite containing a range of useful minerals and materials [20,28]. Research has already used poultry feathers as a polymer filler with a range of plastics such as polypropylene [29], polyethylene [30] and PLA [31], however, it is posited, greater industrial benefit can be attained through generation of a biopolymer.…”
Section: Introductionmentioning
confidence: 99%
“…Around 5.5% (0.112 kg) of a chicken's weight is feathers [25], with annually 6.3 million tonnes being produced as a waste product worldwide. Feathers are currently used in low value uses such as composting, fertilizer or for pet food [26,27] despite containing a range of useful minerals and materials [20,28]. Research has already used poultry feathers as a polymer filler with a range of plastics such as polypropylene [29], polyethylene [30] and PLA [31], however, it is posited, greater industrial benefit can be attained through generation of a biopolymer.…”
Section: Introductionmentioning
confidence: 99%
“…The slopes at five heating rates (5,10,20,30, 40 °C min −1 ) were obtained by plotting lg ⊎ versus 1/T to calculate the activation energy E and analyze the stability of RPUFs. 19 The pyrolysis curves fitted using the Flynn-Wall-Ozawa method and pyrolysis kinetic parameters of the modified RPUFs at different conversions are shown in Fig.…”
Section: Flynn-wall-ozawa Methodsmentioning
confidence: 99%
“…The foam containing keratin and expanded graphite had the highest fire resistance, with a 75% reduction in heat release rate (HRR) compared to VEPUR foam. 5 Liu et al used the redox method to dissolve waste wool to prepare keratin solution and to subject cotton fabrics to flame-retardant treatment. The results showed that the keratin solution prepared by the sodium sulfide reduction method was highly concentrated and had a good flame-retardant effect with an LOI value of 26.5% and a sustained burning time of 2.00 s. 6 Tang et al used ADP to modify the flame-retardant properties of RPUF and investigated the effect of adding different levels of ADP on the flame-retardant properties.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the flame retardants presented, the effectiveness of flame retardant additives in the form of keratin and graphite was also tested, achieving very promising results, whereby, for selected foams, a fourfold reduction in the heat release rate (HRR) was observed [21]. A similar study was also carried out by a Spanish team [22].…”
Section: Introductionmentioning
confidence: 99%